Using Attention-Based Design To Intervene In Decisions To Share Misinformation By Millennials - Amin, Zaid; Ali, Nazlena Mohamad (PT Mattawang Mediatama Solution, 2023)
Having attentive behavior when a user decides to share information on social media is essential. Through such attentive behavior, users are more effectively identify misinformation so that they are not affected by its latent misleading information. In fact, through the vast growth in information in the omnipresence of online media today, increasingly we observe behavioral problems stemming from our one-click habit of easy decision making. This spread of misinformation can literally do severe damage, such as making medical decisions while distracted by receiving COVID-19 misinformation. However, although much research has explored traceability and situation prediction on the spread of misinformation, more research is required to prevent and understand the distraction that exists on human attention, allowing such spreading. Questions arise on how technological interventions can handle the lack of user awareness and when deciding to share information. The research objectives of this study are to investigate and intervene in the role of user attention factors when users decide to share information online. The study uses a mixture of quantitative and qualitative methods. In Study 1, we determined the importance of the attention factor in sharing information on social media by conducting a self-report survey (n=112). We also designed and experimented with a visual selective attention system (VSAS) to intervene in a Millennial’s decision (n=38) by applying an attention-based design approach in Study 2. We conclude that the intervention significantly improved user choices about what they share on online media. Engaging in attentive behavior while sharing information is expected to reduce the spread of misinformation. Furthermore, attentive behavioral factors are needed to form the basis of developing interactions in the design of future social media application systems and produce continuous knowledge that conducts to the non-coercive approach of handling misinformation sharing behavior